Fecal Indicators and Microbial Source Tracking Markers Identify Shared and Site-Specific Contamination Profiles at Freshwater and Marine Beaches - Faizan Saleem; Adam Boere; Amirreza Iranmanesh; Jordan Tustin; Rachel Jardine; Binyam Desta; Thomas A. Edge; Herb E. Schellhorn; Ian Young (Water Research, 2026)

Spatio‐Temporal Resolution of Microbial Functions and Taxa Associated With Cyanobacterial Harmful Algae Blooms Along a 500‐Km Aquatic Continuum in the Lake Erie Watershed - Sophie Crevecoeur; Lori Phillips; Arthur Zastepa; Jérôme Comte; Ngan Diep; Alice Dove; Thomas Edge; Thijs Frenken; R. Michael McKay; Susan B. Waston (Environmental Microbiology, 2025)
Biogeochemical processes rendered by the aquatic microbiome could influence the development of cyanobacterial harmful algal blooms (cHABs), but those biotic factors are poorly understood and rarely considered. We focused on the link between microbial functions, community composition and environmental gradients along the Thames River–Lake St. Clair–Detroit River–Lake Erie corridor across different seasons. We measured the abundance and expression (transcripts) of genes involved in nutrient cycling and microcystin toxin production with qPCR and determined microbial community composition with high‐throughput sequencing of the 16S rRNA gene. Throughout the year, genes and transcripts involved in P acquisition, denitrification and N fixation were in higher abundance upstream in the Thames River and Lake St. Clair. Gene abundance, rather than expression, correlated with environmental variables, but functional changes were linked to changes in the aquatic microbiome and did not respond directly to larger environmental gradients. Network analysis revealed tighter connections between gene expression and biotic variables than gene presence, with ubiquitous and streamlined‐genomes microbes associated with the dominant bloom‐causing cyanobacteria, highlighting the cooperative dynamic of these associations. Overall, the results highlight the link between the changing microbiome, microbial processes and the watershed influence in the presence of cHABs.

Assessment of crAssphage as a human fecal source tracking marker in the lower Great Lakes - Enze Li; Faizan Saleem; Thomas A. Edge; Herb E. Schellhorn (Science of The Total Environment, 2024)

Microbes in beach sands: integrating environment, ecology and public health - Richard L. Whitman; Valerie J. Harwood; Thomas A. Edge; Meredith B. Nevers; Muruleedhara Byappanahalli; Kannappan Vijayavel; João Brandão; Michael J. Sadowsky; Elizabeth Wheeler Alm; Allan Crowe; Donna Ferguson; Zhongfu Ge; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Octopamine and serotonin have opposite effects on antipredator behavior in the orb-weaving spider, Larinioides cornutus - Thomas C. Jones; Tamer S. Akoury; Christopher K. Hauser; Michael F. Neblett; Brent J. Linville; Andrea A. Edge; Nathaniel O. Weber (Journal of Comparative Physiology A, 2011)

High-intensity exercise decreases muscle buffer capacity via a decrease in protein buffering in human skeletal muscle - David Bishop; Johann Edge; Alberto Mendez-Villanueva; Claire Thomas; Knut Schneiker (Pflügers Archiv - European Journal of Physiology, 2009)